First 236U data from the Arctic Ocean and use of 236U/238U and 129I/236U as a new dual tracer - Casacuberta, N; Masque, P; Henderson, G; van der Loeff, M; Bauch, D; Vockenhuber, C; Daraoui, A; Walther, C; Synal, H (Elsevier, 2016)
The first dataset of 236U/238U in the water column of the Arctic Ocean (AO) is presented and shows the widest range of ratios reported so far in the open ocean, from (5±55±5) to (3840±260)×10−12(3840±260)×10−12. Surface samples and depth profiles were collected during two GEOTRACES expeditions in 2011–2012 and analyzed for the concentrations of 236U and 129I, with the aim of investigating whether the combination of 236U/238U and 129I/236U can be used as a new oceanographic tool in the AO. Results show that the distributions of the 236U/238U and 129I/236U atomic ratios are consistent with the different water masses in the AO. High 236U/238U and 129I/236U ratios in the upper water column (>2000×10−12>2000×10−12 and >200, respectively) illustrate the penetration of Atlantic waters (AW) into the AO. Lower values were found in Pacific waters (PW) and deep waters of the AO. Rivers seem to represent a temporally and spatially-constrained third anthropogenic source of 236U but more data are needed to confirm this. In a simple mixing model, the combination of 236U/238U and 129I/236U reveals a high contribution (>99%) of natural background waters (pre-nuclear era) in the deep and bottom waters of the Amerasian basin, indicating an apparent water mass renewal time of >1000 years. Despite the relatively high apparent age of the Amerasian Basin deep waters, this work shows the potential of using the dual-tracer approach as a new oceanographic tool in the Arctic Ocean.